Peran Pendidikan Kewarganegaraan Di Era Globalisasi Dalam Pembentukan Karakter Siswa - Rosalinda Roitona Lubis (Educational Journal, 2026)
This article aims to examine the strategic role of Civic Education in the formation of students' character in the era of globalization which is full of challenges of national values and identity. This study uses a literature review method with a qualitative descriptive approach. Data sources are obtained through critical analysis of theories, previous research results, and relevant documents related to Civic Education and character education. The results of the study indicate that Civic Education plays an important role not only as a means of conveying knowledge about the rights and obligations of citizens, but also as an effective medium in instilling moral values, forming positive habits, and strengthening national identity. Through contextual and continuous learning, this education is able to form students with strong, democratic characters and high national awareness. In conclusion, Civic Education is an important foundation in facing the flow of globalization, as well as being the main instrument in instilling Pancasila values and strengthening national identity among the younger generation.